Wear-resistant concrete based on industrial waste residues and preparation method of wear-resistant concrete
Through the synergistic effect of tungsten slag, ultrafine tungsten slag powder and silicate cement, the fine aggregate and gelling system of hydraulic concrete are optimized, and the problems of impact wear performance and construction difficulty of hydraulic concrete are solved, achieving efficient Improve impact wear performance and environmentally friendly industrial waste slag utilization.
Patent Information
- Application Number
- CN202411197537.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-29
- Publication Date
- 2025-01-14
AI Technical Summary
When the existing technology improves the impact-resistant and wear performance of hydraulic concrete, the low water-adhesive ratio leads to an increase in the risk of concrete cracking, making the construction difficult, and the role of fine aggregate phases is not fully utilized, and technical measures based on tungsten slag industrial waste slag .
Through the synergistic effect of tungsten slag, ultrafine tungsten slag powder and silicate cement, the wear resistance of the fine aggregate phase and cement cement system is optimized, and composite fine aggregate and ultrafine tungsten slag powder of tungsten slag and coarse sand are used. Replace some cement and improve the impact-resistant and wear performance of concrete.
It significantly improves the impact wear performance of hydraulic concrete, solves the recycling problem of waste slag in tungsten slag industry, reduces the risk of hydration heat and cracking, and ensures the workingability and durability of concrete.
Smart Images

Figure CN119306438A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of concrete materials, and in particular to an abrasion-resistant concrete based on industrial waste residues and a preparation method thereof. Background Art
[0002] In the concrete dam of water conservancy facilities, the wear and erosion caused by the impact of high-speed water flow and sediment will increase the surface damage of the concrete, and then cause the concrete of the hydraulic structure to peel off from the surface to the inside, accelerating the deterioration process of the concrete structure. For the hydraulic concrete of the flood discharge system, its anti-abrasion performance is particularly important. The excellent anti-abrasion performance of the flood discharge structure can extend the service life of the concrete structure. The main measures to improve the anti-abrasion performance of the concrete of hydraulic structures mainly include the use of concrete with a lower water-binder ratio, thereby improving the mechanical strength of the hydraulic concrete to resist the erosion of high-speed water flow. This measure has the disadvantage that the low water-binder ratio causes an increase in the amount of concrete cementitious materials, resulting in a higher hydration heat in the concrete, which increases the risk of cracking of the hydraulic concrete. In order to obtain high compressive strength and reduce the hydration heat of concrete as much as possible, a low water-cement ratio is adopted, and high-quality fly ash, silica fume and other active mineral admixtures are used to partially replace cement to improve the overall impact and abrasion resistance of concrete. Even on this basis, a certain amount of steel fiber is added. These measures have caused the workability of concrete to decline, and there are disadvantages such as difficulty in entering the warehouse during construction and difficulty in vibrating and compacting the concrete in the warehouse. There are also hidden dangers such as poor construction effect and failure to achieve the expected improvement in impact and abrasion resistance.
[0003] As a typical multi-phase heterogeneous material, concrete can be considered to be composed of coarse aggregate phase, fine aggregate phase, cement cementitious system paste, etc. In essence, existing measures such as reducing the water-binder ratio and adding high-quality active mineral admixtures are to improve the anti-abrasion performance of concrete by optimizing the mechanical properties of the cement cementitious system paste phase. These measures ignore the role of the fine aggregate phase. Tungsten slag is a solid waste generated in the production of ammonium paratungstate. In recent years, with the mining of tungsten ore, the output of tungsten slag has been increasing. Tungsten slag has high hardness and good physical and chemical stability. The fineness modulus of tungsten slag produced by the production of ammonium paratungstate is about 0.60 according to the artificial sand fineness modulus characterization method, which belongs to the category of ultra-fine sand fineness. Based on this, the tungsten slag can be compounded with the coarse sand with a fineness modulus of more than 3.2 discarded from the sand and gravel system processing as fine aggregate in hydraulic anti-abrasion concrete, thereby improving the wear resistance of the fine aggregate phase; at the same time, based on the high hardness of tungsten, the tungsten slag with a fineness modulus of 0.60 is ground and ultra-finely processed to obtain ultra-fine tungsten slag powder, and the ultra-fine tungsten slag powder is used to replace fly ash, silica fume and other mineral admixtures to replace part of the cement in the anti-abrasion concrete, thereby improving the wear resistance of the cement cementitious system paste, and finally improving the anti-abrasion performance of hydraulic concrete. Compared with the existing technical measures to improve the anti-abrasion performance of concrete, there are no technical measures and research applications based on tungsten slag industrial waste to improve the anti-abrasion performance of hydraulic concrete. Summary of the invention
[0004] In view of the problems existing in the above-mentioned background technology, the present invention provides an abrasion-resistant concrete based on industrial waste slag with excellent abrasion resistance and a preparation method thereof. Through the synergistic effect of tungsten slag, ultrafine tungsten slag powder and silicate cement, the overall abrasion resistance of concrete is improved from the perspective of improving the abrasion resistance of the fine aggregate phase and the pure slurry phase of the cement cementitious system of hydraulic concrete. It not only solves the problem of recycling of tungsten slag industrial waste, but also provides a new technical direction for improving the abrasion resistance of hydraulic concrete, which is easy to promote and use.
[0005] In order to achieve the purpose of the present invention, the following technical scheme is adopted:
[0006] An abrasion-resistant concrete based on industrial waste residues comprises the following components, each component being measured by weight:
[0007] Coarse aggregate 1050-1200 parts,
[0008] 480-550 parts of coarse sand,
[0009] 135-210 parts of tungsten slag,
[0010] 300-360 parts of Portland cement,
[0011] 75-90 parts of ultra-fine tungsten slag powder,
[0012] High performance water reducing agent 1-1.5 parts,
[0013] 140-160 parts of water;
[0014] The tungsten slag is obtained by drying the industrial waste tungsten slag produced by the production of ammonium paratungstate at 80°C to constant weight, and the fineness modulus of the tungsten slag measured by the artificial sand fineness modulus characterization method is 0.50-0.60;
[0015] The ultrafine tungsten slag powder is obtained by grinding the above tungsten slag, and its fineness is 1% to 5% of the residue on a 45μm sieve;
[0016] The coarse aggregate includes small stones with a particle size of 5-20 mm and medium stones with a particle size of 20-40 mm, and the mixing mass ratio of the two is 1:1; when the ratio of small stones to medium stones is 1:1, the coarse aggregate has a continuous particle size distribution as a whole.
[0017] Furthermore, the present invention prepares fine aggregate by adjusting the ratio of tungsten slag to coarse sand. When the proportion of tungsten slag is 135-210 parts and the proportion of coarse sand is 480-550 parts, it is determined that the fineness modulus of the composite fine aggregate mixed with tungsten slag and coarse sand is controlled at 2.3-3.0, and the particle sieve classification distribution curve falls in zone II. The composite fine aggregate can better meet the requirements of artificial sand for concrete.
[0018] Furthermore, the coarse sand described in the present invention is artificial sand or natural sand with a fineness modulus of 3.2 to 3.6.
[0019] Furthermore, the silicate cement and high-performance water reducing agent described in the present invention are qualified products that meet the requirements of their respective national standards.
[0020] Furthermore, in the admixture, ultrafine tungsten slag powder with a fineness controlled at 1% to 5% of the residue on a 45 μm sieve is used to replace cement at 10% to 20% of the mass of cement in each cubic meter of concrete.
[0021] The impact-resistant concrete of the present invention has been proven through a concrete impact-resistant performance test that the impact-resistant concrete can significantly improve the concrete impact-resistant performance compared with the concrete with the same water-binder ratio and the same cementitious material dosage according to the present invention.
[0022] Furthermore, the present invention also provides a method for preparing abrasion-resistant concrete based on industrial waste residues, comprising the following steps:
[0023] (1) Powder mixing: Mix silicate cement and ultrafine tungsten slag powder in proportion using a double-motion mixing device and use them as finished powder for later use;
[0024] In step (1), the vibration frequency of the mixing equipment is controlled to be 20-30 Hz, the rotation speed is 15-20 r / min, the inclination angle of the mixer worktable is 10°-15°, and the mixing time is 2h-4h;
[0025] (2) The powder material of step (1) is weighed in proportion and put into a concrete mixer, and then the composite fine aggregate formed by mixing coarse aggregate, coarse sand and tungsten slag is successively put into the concrete mixer in proportion, and the mixer is started for dry mixing for 2 to 3 minutes;
[0026] (3) adding the water and high-performance water reducing agent mixed in proportion in step (2) and stirring in a concrete mixer for 180 seconds to complete the mixing of the abrasion-resistant concrete;
[0027] (4) Mix concrete in accordance with the method specified in the "Test Procedure for Hydraulic Concrete" (DL / T 5150-2017). The molding and curing of concrete abrasion resistance specimens shall be carried out in accordance with the "Test Procedure for Hydraulic Concrete" (DL / T 5150-2017).
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] (1) The abrasion-resistant concrete based on industrial waste slag provided by the present invention optimizes the wear resistance of the fine aggregate phase and the pure slurry phase of the cementitious system of the concrete respectively by relying on the high hardness physical property of the tungsten element, thereby improving the abrasion resistance of the hydraulic concrete as a whole, and making full use of the tungsten slag industrial waste, which has good social and environmental benefits and engineering application value;
[0030] (2) The impact-resistant concrete of the present invention uses ultrafine tungsten slag powder to partially replace cement, which improves the durability of the cementitious system while reducing the amount of cement, indirectly reducing the hydration temperature rise and cracking risk of the concrete; in addition, a micro-grading effect is formed between the ultrafine tungsten slag powder and the cement particles, which promotes the close stacking of the powders and ensures that the workability of the concrete is not reduced. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a screening curve diagram of the composite sand of tungsten slag and coarse sand described in the present invention.
[0032] Figure 2 This is a comparison of the surface morphology of the abrasion-resistant concrete based on industrial waste residue before and after the abrasion test described in Example 1 of the present invention.
[0033] Figure 3 This is a comparison of the surface morphology of the ordinary abrasion-resistant concrete before and after the abrasion test described in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0034] The present application is further described in detail below with reference to the embodiments.
[0035] The components in the specific embodiments of the present application can all be obtained from the market. Among them, tungsten slag produced by the production of ammonium paratungstate (APT); commercially available artificial coarse sand; cement is ordinary Portland cement of P·O 42.5 grade; polycarboxylate water reducer is PCA-1 type; coarse aggregate is divided into 5-20mm small stone and 20-40mm medium stone, and the mass ratio of small stone to medium stone is 1:1.
[0036] Example 1
[0037] A kind of impact-resistant concrete, comprising the following components in parts by weight:
[0038] 145 parts of water, 326 parts of cement, 1071 parts of coarse aggregate (the ratio of small and medium stones is 1:1), 502 parts of coarse sand, 1.2 parts of polycarboxylate water reducer, 180 parts of tungsten slag, and 75 parts of ultrafine tungsten slag powder. According to the measurement, the coarse sand fineness modulus is 3.4, the tungsten slag fineness modulus is 0.52, and the ultrafine tungsten slag fineness is 2% on a 45μm sieve.
[0039] A method for preparing abrasion-resistant concrete comprises the following steps:
[0040] (1) Powder mixing: Mix silicate cement and ultrafine tungsten slag powder in proportion using a double-motion mixing device and use them as finished powder for later use;
[0041] In step (1), the vibration frequency of the mixing equipment is controlled to be 20-30 Hz, the rotation speed is 15-20 r / min, the inclination angle of the mixer worktable is 10°-15°, and the mixing time is 2h-4h;
[0042] (2) The powder material of step (1) is weighed in proportion and put into a concrete mixer, and then the composite fine aggregate formed by mixing coarse aggregate, coarse sand and tungsten slag is successively put into the concrete mixer in proportion, and the mixer is started for dry mixing for 2 to 3 minutes;
[0043] (3) adding the water and high-performance water reducing agent mixed in proportion in step (2) and stirring in a concrete mixer for 180 seconds to complete the mixing of the abrasion-resistant concrete;
[0044] (4) Mix concrete in accordance with the method specified in the "Test Procedure for Hydraulic Concrete" (DL / T 5150-2017). The molding and curing of concrete abrasion resistance specimens shall be carried out in accordance with the "Test Procedure for Hydraulic Concrete" (DL / T 5150-2017).
[0045] Example 2
[0046] The difference between Example 2 and Example 1 is that:
[0047] 155 parts of water, 316 parts of cement, 1121 parts of coarse aggregate (the ratio of small and medium stones is 1:1), 540 parts of coarse sand, 1.2 parts of polycarboxylate water reducer, 140 parts of tungsten slag, and 85 parts of ultrafine tungsten slag powder. According to the measurement, the coarse sand fineness modulus is 3.2, the tungsten slag fineness modulus is 0.55, and the ultrafine tungsten slag fineness is 2% on a 45μm sieve.
[0048] Example 3
[0049] The difference between Example 3 and Example 1 is that:
[0050] 155 parts of water, 310 parts of cement, 1182 parts of coarse aggregate (the ratio of small and medium stones is 1:1), 480 parts of coarse sand, 1.4 parts of polycarboxylate water reducer, 200 parts of tungsten slag, and 90 parts of ultrafine tungsten slag powder. It has been determined that the coarse sand fineness modulus is 3.6, the tungsten slag fineness modulus is 0.55, and the ultrafine tungsten slag fineness is 5% on a 45μm sieve.
[0051] Comparative Example 1
[0052] The difference between Comparative Example 1 and Example 1 is that: no tungsten slag and ultrafine tungsten slag powder are added in the mix ratio, the same water-cement ratio and the same cementitious material dosage are 145 parts of water, 400 parts of cement, 1071 parts of coarse aggregate (the ratio of small and medium stones is 1:1), 680 parts of coarse sand, and 1.2 parts of polycarboxylic acid water reducer.
[0053] Comparative Example 2
[0054] The difference between Comparative Example 2 and Example 1 is that: no ultrafine tungsten slag powder is added in the mix ratio to replace cement, and the dosage of each component is 145 parts of water, 1.2 parts of polycarboxylic acid water reducer, 400 parts of cement, 1071 parts of coarse aggregate (the ratio of small and medium stones is 1:1), 502 parts of coarse sand, and 180 parts of tungsten slag.
[0055] Comparative Example 3
[0056] The difference between Comparative Example 3 and Example 2 is that the tungsten slag content in the mix ratio is relatively high, with an admixture of 248 parts, and the admixtures of the other components are 155 parts of water, 1.2 parts of polycarboxylic acid water reducer, 316 parts of cement, 85 parts of ultrafine tungsten slag, 1121 parts of coarse aggregate (the ratio of small to medium stone is 1:1), and 430 parts of coarse sand.
[0057] Comparative Example 4
[0058] The difference between Comparative Example 4 and Example 2 is that the content of ultrafine tungsten slag powder in the mix ratio is relatively high, with an admixture of 100 parts, and the admixtures of the other components are 155 parts of water, 1.2 parts of polycarboxylic acid water reducer, 300 parts of cement, 1121 parts of coarse aggregate (the ratio of small to medium stone is 1:1), 540 parts of coarse sand, and 140 parts of tungsten slag.
[0059] Comparative Example 5
[0060] The difference between Comparative Example 5 and Example 3 is that there is a difference in the grading of coarse aggregate in the mix ratio, the amount of tungsten slag is 200 parts, coarse sand is 480 parts, small stone is 450 parts, medium stone is 730 parts, water is 155 parts, cement is 310 parts, polycarboxylate water reducer is 1.4 parts, and ultrafine tungsten slag is 90 parts.
[0061] Comparative Example 6
[0062] The difference between Comparative Example 6 and Example 3 is that there is a difference in the grading of fine aggregate in the mix ratio, the ratio of tungsten slag to coarse sand is 1:1, wherein the amount of tungsten slag is 340 parts, coarse sand is 340 parts, coarse aggregate is 1182 parts (the ratio of small and medium stones is 1:1), water is 155 parts, cement is 310 parts, polycarboxylate water reducer is 1.4 parts, and ultrafine tungsten slag is 90 parts.
[0063] Performance Testing
[0064] The preparation and performance testing of the concrete of each embodiment and comparative example of the present invention were carried out according to the concrete compressive strength and abrasion resistance tests specified in the "Testing Procedure for Hydraulic Concrete" (DL / T5150-2017). The test results are shown in Table 1.
[0065] Table 1 Concrete performance test results
[0066]
[0067]
[0068] According to the performance comparison between Examples 1-3 and Comparative Examples 1-6, it can be seen that the tungsten slag dosage and aggregate gradation have a great influence on the concrete performance.
[0069] Compared with Example 1-2, the addition of tungsten slag and ultrafine tungsten slag powder in Example 1 can effectively improve the 28d compressive strength and abrasion resistance of concrete, and the wear rate is effectively reduced. The addition of ultrafine tungsten slag powder ensures the workability of concrete.
[0070] Compared with comparative examples 3-4, the addition of tungsten slag in Example 2 can improve the abrasion resistance of concrete and reduce the wear rate, but too high a tungsten slag content will reduce the slump of concrete, which will have an adverse effect on the workability of concrete and affect the cement hydration process, thereby affecting the strength development of concrete after hardening. Too high a content of ultrafine tungsten slag powder will reduce the abrasion resistance of concrete;
[0071] In Example 3, compared with Comparative Examples 5-6, the fineness modulus of the fine aggregate mixed with tungsten slag and coarse sand is in the range of 2.3-3.0, and the grading of the small stone-medium stone ratio of 1:1 has a favorable effect on the development of concrete strength.
[0072] Figure 2 and Figure 3The following are the surface morphology comparison diagrams of the abrasion-resistant concrete before and after the abrasion test of Example 1 and Comparative Example 1, respectively. Figure 2 , Figure 3 In contrast, the concrete specimen added with tungsten slag in Example 1 of the present invention has a smaller wear depth on the surface than ordinary concrete after the anti-impact and abrasion test, and the surface is smoother; the high hardness of tungsten slag enhances the wear resistance of concrete, reduces the wear of cement paste in the anti-impact and abrasion test, and slows down the wear process of coarse aggregate.
Claims
1. A wear-resistant concrete based on industrial waste residue, characterized in that: It includes the following components, each component is calculated by weight: Coarse aggregate 1050-1200 parts, 480-550 parts of coarse sand, 135-210 parts of tungsten slag, 300-360 parts of Portland cement, 75-90 parts of ultra-fine tungsten slag powder, High performance water reducing agent 1-1.5 parts, 140-160 parts of water; The tungsten slag is obtained by drying the industrial waste tungsten slag produced by the production of ammonium paratungstate at 80°C to constant weight, and the fineness modulus of the tungsten slag measured by the artificial sand fineness modulus characterization method is 0.50-0.60; The ultrafine tungsten slag powder is obtained by grinding the above tungsten slag, and its fineness is 1% to 5% of the residue on a 45μm sieve; The coarse aggregate includes small stones with a particle size of 5-20 mm and medium stones with a particle size of 20-40 mm, and the mixing mass ratio of the two is 1:
1.
2. The abrasion-resistant concrete based on industrial waste residue according to claim 1, characterized in that: The fineness modulus of the composite fine aggregate mixed with the tungsten slag and coarse sand is controlled at 2.3-3.0, and the particle sieving distribution curve falls in zone II.
3. The abrasion-resistant concrete based on industrial waste residue according to claim 1, characterized in that: The coarse sand is artificial sand or natural sand with a fineness modulus of 3.2 to 3.
6.
4. The abrasion-resistant concrete based on industrial waste residue according to claim 1, characterized in that: The silicate cement and high-performance water reducing agent are qualified products that meet the requirements of their respective national standards.
5. The abrasion-resistant concrete based on industrial waste residue according to claim 1, characterized in that: The ultrafine tungsten slag powder with a fineness controlled at 1% to 5% of the residue on a 45 μm sieve can replace cement at 10% to 20% of the cement mass in each cubic meter of concrete.
6. A method for preparing the abrasion-resistant concrete based on industrial waste residues according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) Powder mixing: Mix silicate cement and ultrafine tungsten slag powder in proportion using a double-motion mixing device and use them as finished powder for later use; In step (1), the vibration frequency of the mixing equipment is controlled to be 20-30 Hz, the rotation speed is 15-20 r / min, the inclination angle of the mixer worktable is 10°-15°, and the mixing time is 2h-4h; (2) The powder material of step (1) is weighed in proportion and put into a concrete mixer, and then the composite fine aggregate formed by mixing coarse aggregate, coarse sand and tungsten slag is successively put into the concrete mixer in proportion, and the mixer is started for dry mixing for 2 to 3 minutes; (3) Add water and high-performance water reducing agent in proportion to the mixer after dry mixing; (4) Mix concrete in accordance with the method specified in the "Test Procedure for Hydraulic Concrete" (DL / T 5150-2017). The molding and curing of concrete abrasion resistance specimens shall be carried out in accordance with the "Test Procedure for Hydraulic Concrete" (DL / T 5150-2017).
Citation Information
Cited By
Functional mineral admixture as well as preparation method and application thereof
CN121494399A
Anti-abrasion solid waste-based concrete for canal ship lock gallery and preparation method of anti-abrasion solid waste-based concrete
CN121990796A